Identification of two quantitative genes controlling soybean flowering using bulked-segregant analysis and genetic mapping - Lv, Tianxiao; Wang, Lingshuang; Zhang, Chunyu; Liu, Shu; Wang, Jinxing; Lu, Sijia; Fang, Chao; Kong, Lingping; Li, Yunlong; Li, Yuge; Hou, Xingliang; Liu, Baohui; et al. (Frontiers in Plant Science, 2022)
Photoperiod responsiveness is important to soybean production potential and adaptation to local environments. Varieties from temperate regions generally mature early and exhibit extremely low yield when grown under inductive short-day (SD) conditions. The long-juvenile (LJ) trait is essentially a reduction and has been introduced into soybean cultivars to improve yield in tropical environments. In this study, we used next-generation sequencing (NGS)-based bulked segregant analysis (BSA) to simultaneously map qualitative genes controlling the LJ trait in soybean. We identified two genomic regions on scaffold_32 and chromosome 18 harboring loci LJ32 and LJ18, respectively. Further, we identified LJ32 on the 228.7-kb scaffold_32 as the soybean pseudo-response-regulator gene TOF11 and LJ18 on a 301-kb region of chromosome 18 as a novel PROTEIN FLOWERING LOCUS T-RELATED gene, Glyma.18G298800. Natural variants of both genes contribute to LJ trait regulation in tropical regions. The molecular identification and functional characterization of TOF11 and LJ18 will enhance understanding of the molecular mechanisms underlying the LJ trait and provide useful genetic resources for soybean molecular breeding in tropical regions.